Guidelines for the Management of Satitsarmukkee School Games - Sumon, Sasathorn; Luksanapisut, Prapat (Academic Journal of Thailand National Sports University, 2013)
The study of guidelines for the management of Satitsamukkee School Games will be developed the guidelines for the management of Satitsamukkee School Games to achieve objectives. Purpose The purpose of this research was to develop the guidelines for the management of Satitsamukkee School Games Methods Two groups of experts and/or specialists were selected as the samples for interviews and Delphi Future Research questionnaires. The research’s tools were interviews and questionnaires in 12 aspects; rules and regulations, venues, sports technique, results report, ceremony, public relations, medical and nurse, audio-visual aids, reception, food and drink, transportation and safety and accommodation. A twostage sequence was conducted as the research processing. In the first stage, the first group of 5 experts and/or specialists was interviewed to collect data on conditions, problems and needs of guidelines for the management of Satitsamukkee School Games. The obtained data from the first stage study were used to create the four level rating scale questionnaires on the guidelines of developing the management of Satitsamukkee School Games. In the second stage, the Delphi Future Research Technique were applied to study. The questionnaires created from the first stage study were used to collect data from the second group of 17 experts and/or specialists in order to evaluate the possibility in developing guidelines for the management of Satitsamukkee School Games. All obtained data from both stage studies were statistically analyzed in terms of frequency, mean and standard deviation and presented in the form of tables with description. Result The research results found that the guidelines for developing the management of Satitsamukkee School Games in 12 aspects were possible in application to develop guidelines for the management of Satitsamukkee School Games to achieve objectives in the highest level, mean 3.95 and standard deviation .07 Conclusion There were 33 possible guidelines to achieve the objectives in the highest level for the management of Satitsamukkee School Games; consisting of 4 guidelines in medical and nurse aspect, 3 guidelines in each aspect of sports technique: rules and regulations, venues, accommodation, results report, public relations, transportation and safety and audio-visual aids, 2 guidelines in each aspect of food and drink and ceremony and 1 guideline in reception aspect.